Making research matter : a psychologist's guide to public engagement - Tropp, Linda R. (American Psychological Association, 2018)
"This volume gathers well-known experts to discuss how researchers can impact a broader audience, by lending their scientific expertise to pressing social issues, current events, and public debates. The landmark Brown v. Board of Education case, in which the Supreme Court cited psychological evidence in overturning school segregation, is just one example of the positive and noteworthy impact social science research can have on the world beyond academia. But many researchers today have trouble communicating with non-academic audiences and engaging the broader society. With pointers on talking to the media, testifying as an expert witness, dealing with governmental organizations, working with schools and students, and influencing public policy, this volume helps social scientists forge the vital link between scholarship and social engagement. Contributors include prominent experts from a wide-range of specialties, such as academic psychologists, Harvard Business School professors, directors of organizations, and government officials."--Preface. (PsycINFO Database Record (c) 2017 APA, all rights reserved)